Review: Use of human-edible animal feeds by ruminant livestock. (12th September 2017) - Wilkinson, J. M.; Lee, M. R. F.
Abstract : The drive to increase the output of animal product in some sectors of ruminant livestock production has led to greater use of feeds such as cereal grains and soyabean meal that are potentially human-edible. This trend has caused concern since, by so doing, ruminants compete not only with monogastric livestock but also with the human population for a limited global area of cultivatable land on which to produce grain crops. Reasons for using potentially human-edible feeds in ruminant diets include increased total daily energy intake, greater supply of essential amino acids and improved ruminal balance between fermentable energy and degradable protein. Soyabean meal, produced on land that has been in arable cultivation for many years can fulfil a useful role as a supplier of undegraded dietary protein in diets for high-yielding dairy cows. However, in the context of sustaining the production of high-quality foods from livestock to meet the demands of a growing human population, the use of potentially human-edible feed resources by livestock should be restricted to livestock with the highest daily nutrient requirements; that is, potentially human-edible feed inputs should be constrained to meeting requirements for energy and protein and to rectifying imbalances in nutrient supply from pastures and forage crops such as high concentrations of nitrogen (N). There is therefore a role for human-edible feeds in milk production because forage-only systems are associated with relatively low output per head and also low N use efficiency compared with systems with greater reliance on human-edible feeds. Profitability on farm is driven by control of input costs as well as product value and examples are given of low-cost bovine milk and meat production with little or no reliance on potentially human-edible feeds. In beef production, the forage-only systems currently under detailed real-time life-cycle analysis at the North Wyke Farm Platform, can sustain high levels of animal growth at low feed cost. The potential of all-forage diets should be demonstrated for a wide range of ruminant milk and meat production systems. The challenge for the future development of ruminant systems is to ensure that potentially human-edible feeds, or preferably human-inedible by-products if available locally, are used to complement pastures and forage crops strategically rather than replace them.